Body petrification in Italy. Another recipe of the 19th century revealed. - Larentis, Omar; Tesi, Chiara; Licata, Marta; Fusco, Roberta; Gorini, Ilaria; Rossetti, Chiara; Tonina, Enrica (Medicina Historica, 2021)
The embalming of bodies through various techniques and materials characterized the paths of some Italian scholars between the 19th and 20th century. The so-called petrifiers developed their own formulas and methods, which have so far remained mostly unknown. In this article, we present one of the formulas used in Italy between the 19th and 20th centuries. This recipe increases our knowledge of embalming practices and may well prove useful for the conservation and protection of ancient anatomical preparations, which should be regarded as unique and priceless assets.